Expression of peptides encoded by exons in cloned mammalian DNA - Kreißig, Sabine; Kutsche, Kerstin; Dear, Neil; Boehm, Thomas (Nucleic acids research, 1996)
New synthetic approaches, such as combinatorial chemistry, provide a rich source of potential drug candidates. At the same time, the human genome initiative and other large-scale sequencing projects provide a large number of novel drug targets. However, the functional analysis of thousands of new genes remains a major challenge for the future. A systematic strategy for genome-wide functional analysis of genes could employ the fact that at least some modules in multi-domain proteins are encoded in individual exons. Exon amplification provides information about coding regions of most genes that is independent of their transcriptional status; exon amplification from entire mammalian genomes has been demonstrated. Here, we describe the development of an exon-trap system, λGEE (for genomic exon expression), that couples exon amplification with the expression of exon-encoded peptides.